Culture in Digital Format - Szűcs, Olga; Tanatova, Dina; Yudina, Tatyana (Slavica, 2019)
The article analyzes the changes in traditional culture triggered by technologies and development of its new formats as a result, such as clip culture, screen culture, culture of computer games, etc. It touches upon the influence on culture of the personal computer and other numerous digital devices, in particular the Internet, artificial intelligence, computer graphics, and virtual reality. Traditional means of communication (books, photographs, audio and video recordings, digital TV, etc.) that are most influenced by digital technologies are also discussed. As traditional culture is losing its original features that emphasize the difference between different peoples, societies and their individual characteristics, all these processes are extensive, generating not only progressive, but negative trends. On the one hand modern culture has become accessible to everybody, on the other hand, it has lost the «romance» of personal communication. The article points out that nowadays the investigation of culture in digital format does not primarily mean analyzing its phenomena and artifacts in themselves. It is rather a matter of monitoring further transformations and contributing the unique features of traditional culture preservation, without diminishing the importance of digital technologies as a whole in society.